Melan-A/MART-1(51–73) represents an immunogenic HLA-DR4-restricted epitope recognized by melanoma-reactive CD4(+) T cells - Zarour, Hassane M. (The National Academy of Sciences, 2000)
The human Melan-A/MART-1 gene encodes an HLA-A2-restricted peptide epitope recognized by melanoma-reactive CD8(+) cytotoxic T lymphocytes. Here we report that this gene also encodes at least one HLA-DR4-presented peptide recognized by CD4(+) T cells. The Melan-A/MART-1(51–73) peptide was able to induce the in vitro expansion of specific CD4(+) T cells derived from normal DR4(+) donors or from DR4(+) patients with melanoma when pulsed onto autologous dendritic cells. CD4(+) responder T cells specifically produced IFN-γ in response to, and also lysed, T2.DR4 cells pulsed with the Melan-A/MART-1(51–73) peptide and DR4(+) melanoma target cells naturally expressing the Melan-A/MART-1 gene product. Interestingly, CD4(+) T cell immunoreactivity against the Melan-A/MART-1(51–73) peptide typically coexisted with a high frequency of anti-Melan-A/MART-1(27–35) reactive CD8(+) T cells in freshly isolated blood harvested from HLA-A2(+)/DR4(+) patients with melanoma. Taken together, these data support the use of this Melan-A/MART-1 DR4-restricted melanoma epitope in future immunotherapeutic trials designed to generate, augment, and quantitate specific CD4(+) T cell responses against melanoma in vivo.